Strategi Komunikasi Organisasi Teater Sunda Kiwari dalam Menyukseskan Festival Drama Basa Sunda (FDBS) XXII Tahun 2024 - Andriansah (KOMUNIKA BANGSA, 2025)
This study aims to describe the organizational communication strategy of the Kiwari Sundanese Theatre in ensuring the success of the 22nd Sundanese Drama Festival (FDBS) in 2024. The research approach used was qualitative with descriptive methods, through in-depth interviews, observations, and documentation studies of administrators, members, and related parties in organizing the festival. The results of the study indicate that the Kiwari Sundanese Theatre implements a structured organizational communication strategy in three main dimensions: internal communication, external communication, and public communication. Internal communication is carried out through regular meetings, online groups, and a clear division of tasks to strengthen coordination between members. External communication is realized in collaboration with the Government, sponsors, the media, and other arts communities as an effort to expand networks and support. Meanwhile, public communication is focused on promoting the festival through social media, radio broadcasts, and creative campaigns based on local wisdom to attract the attention of the wider community. The implemented strategy is considered effective in increasing participation, enthusiasm, and the success of the 22nd FDBS. This study recommends strengthening digital-based communication innovation and increasing human resource capacity within the organization to face the challenges of organizing festivals in the future.